(untitled) (Research, Society and Development, 2022)
Adolescence is a phase of great psychological, social, and biological changes. The World Health Organization considers that this phase comprises the period from 10 to 19 years of age and it is during this period that human beings build habits, which will most likely be carried into adulthood. The objective of this study was to identify oral health risks in adolescents, the importance given by this group to oral health and the factors that interfere positively or negatively in satisfactory oral health indicators. To this end, a literature review was conducted with articles published between the years 2012 and 2022, with the theme of adolescence and focus on oral health. It was noticed that the promotion of health and healthy habits in this phase is of utmost importance, aiming at raising awareness among adolescents and reducing damage.It was verified that regarding oral health, dental caries is the main disease observed in adolescence, followed by periodontal disease with a focus on gingivitis and malocclusions. Socioeconomic conditions, parents’ level of education, obesity, self-esteem problems, female hormonal changes, and the use of licit and illicit drugs are factors that directly influence the oral health of adolescents. More studies are needed in the field of adolescence, since this phase of many transformations requires constant study and updating of health professionals, who should have the means, through high-impact studies, to base their practice on scientific evidence.